2014
DOI: 10.3844/jssp.2014.51.62
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Mobile-Learning Adoption Intention: An Empirical Investigation in High Education

Abstract: This study investigates the use of mobile phones and tablets for learning purposes among university students in Vietnam. For this purpose, the research is based on relevant technology acceptance literature and the Technology Acceptance Model (TAM) is proposed to analyze the adoption of mobile devices and smart phones by Vietnam students for accessing course materials, searching the web for information related to their discipline, sharing knowledge, conducting assignments etc. Employing structural equation mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
26
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 31 publications
9
26
0
1
Order By: Relevance
“…This was also noticed through the mean value provided in Table III use. This is contrary to popular belief in m-learning literature that showed technological restrictions seemed not to induce significant usability problems inhibiting m-learning adoption [7]. Our result had supported [7] who concluded that PU had the highest path coefficient and remained strong predictors of behavioral intention and attitude to use.…”
Section: Discussionsupporting
confidence: 46%
See 4 more Smart Citations
“…This was also noticed through the mean value provided in Table III use. This is contrary to popular belief in m-learning literature that showed technological restrictions seemed not to induce significant usability problems inhibiting m-learning adoption [7]. Our result had supported [7] who concluded that PU had the highest path coefficient and remained strong predictors of behavioral intention and attitude to use.…”
Section: Discussionsupporting
confidence: 46%
“…This is contrary to popular belief in m-learning literature that showed technological restrictions seemed not to induce significant usability problems inhibiting m-learning adoption [7]. Our result had supported [7] who concluded that PU had the highest path coefficient and remained strong predictors of behavioral intention and attitude to use.These results validate the power of TAM constructs and its appropriateness in predicting acceptance of mobile learning. The relationship between PEOU and PU also confirmed [10] as well as the other relationship with TAM had also been confirmed.…”
supporting
confidence: 46%
See 3 more Smart Citations